Nutritional supplement usage in patients admitted to a spinal cord injury center. (November 2013) - Wong, Samford; Graham, Allison; Green, Debbie; Hirani, Shashivadan P.; Forbes, Alastair
Abstract : Objectives: To (1) assess food intake; (2) establish the prevalence of dietary supplement usage and its associated cost (oral nutritional supplements (ONS); vitamin and mineral supplements (VMS)) and; (3) identify the characteristics of nutritional supplement users among patients admitted to a spinal cord injury (SCI) center. Study design: A single center survey. Methods: Standardized questionnaires were used to collect demographic information, food consumption over a 24-hour period, and the use of nutritional supplements. Multivariate logistic regression was used to determine the characteristics of dietary supplement usage and those using them. Results: Seventy-three patients with SCI completed and returned the questionnaires (69.5% response rate). From 67 questionnaires with food intake data, 21 patients (31.3%) consumed three full meals a day. Nine of the full 73 patients (12.3%) received artificial nutritional support, 14 of 73 (19.1%) received ONS, 34 of 73 (46.5%) received VMS, and 31 of 73 (42.4%) required assistance in order to eat. The three supplements most often prescribed were multivitamins (19.1%), vitamins B (17.8%), and vitamin D (13.6%). VMS use was associated with age (years: >60 vs. ≤60: 62.1 vs. 34.1%, P = 0.019), nutrition risk (Spinal Nutrition Screening Tool (≥11 vs. <11: 65.7 vs. 28.9%, P = 0.001), and serum albumin concentration (<35 vs. ≥35 g/l: 59.6 vs. 16%, P < 0.01). Patients at nutrition risk were found to consume more ONS than the lower risk group (28.5 vs. 10.5%, P = 0.05). The expenditures on ONS and VMS were higher in the group at greater nutritional risk (£1878.3 vs. £914.3, P = 0.005). Conclusion: The use of nutritional supplements is common in patients with SCI, particularly in older adults and patients with poor nutritional state. However, the present study identified only small numbers of patients consuming all of their hospital meals, which may well contribute to undernutrition risk. Given that a high proportion of patients with SCI require assistance to eat, we suggest that further efforts focus on the feasibility of providing feeding assistants, and on reviewing the nature of the hospital menu.